Exploring Coronary Artery Disease GWAs Targets With Functional Links to Immunometabolism - Hughes, Maria F.; Lenighan, Yvonne M.; Godson, Catherine; Roche, Helen M. (Frontiers in Cardiovascular Medicine, 2018)
Finding genetic variants that cause functional disruption or regulatory change among the many implicated GWAs variants remains a key challenge to translating the findings from GWAs to therapeutic treatments. Defining the causal mechanisms behind the variants require functional screening experiments that can be complex and costly. Prioritising variants for functional characterisation using techniques that capture important functional and regulatory elements can assist this. The genetic architecture of complex traits such as cardiovascular disease (CVD) and type II diabetes (T2D) comprise an enormously large number of variants of small effect contributing to heritability and spread throughout the genome. This makes it difficult to distinguish which variants or core genes are most relevant for prioritisation and how they contribute to the regulatory networks that become dysregulated leading to disease. Despite these challenges, recent GWAs for CAD prioritised genes associated with lipid metabolism, coagulation and adhesion along with novel signals related to adipogenesis, vascular function and innate immunity as important core drivers of risk. We focus on three examples of novel signals associated with CAD which affect risk through missense or UTR mutations indicating their potential for therapeutic modification. These variants play roles in adipogenesis, vascular dysfunction and innate immunity which form the cornerstones of immuno-metabolism. In addition we have explored the putative, but potentially important interactions between the environment, specifically food and nutrition, with respect to key processes.